Evaluation of biochemical, nutrient content and productivity of oyster mushrooms biofortified with Zinc Oxide Nanoparticles - Leema; Garg, Shivanshu; Gupta, Deepanjali; Punetha, Himanshu; Akhter, Fareeda; Gangola, Saurabh; Bhandari, Geeta; Mittal, Amit; Siddiqui, Sazada (Frontiers in Sustainable Food Systems, 2025)
In the current investigation, a successful effort has been implemented to bio-fortify Pleurotus djamor and Pleurotus florida with ZnONPs (Zinc Oxide Nanoparticles) for nutritional enrichment trial during two consecutive years 2020–2021. Two concentrations of ZnONPs, 20 and 40 ppm were added into the substrate at the spawning stage and their effect was monitored by measuring the physical attributes like mycelium radial growth, morphology (pilus length, pilus diameter, stipe length and stipe width) with biochemical analysis (anti-oxidative enzymes, phenols, flavonoids and total antioxidants) and nutritional analysis (macronutrients, micronutrients, protein content and total soluble sugar) of extracts obtained from the Zn (zinc) fortified Oyster mushrooms. Results have shown an improvement in the mycelial growth and yield of two Pleurotus spp. studied here, while the effect of ZnONPs on morphology varied positively with the concentrations used and the type of oyster mushroom. The anti-oxidative enzymes were found to be triggered upon application of ZnONPs reflecting the role of ZnONPs in activating the enzymes and thereby enhanced potential in free radical scavenging activity. Along with these the phenols, flavanoids and anti-oxidants were also found to be elevated upon application of ZnONPs. An enhancement in macro- and micro-nutrient concentration has justified the utilization of ZnONPs in biofortification. In near future, more emphasis should be laid on ZnONPs enriched biofortified mushrooms to boost nutritive potential of edible mushrooms and to encounter the ever growing metabolic deficiency problems with the increasing human population in the world.